Influence of the previous antihypertensive therapy on the course of cerebral stroke - I. G. Kolchu; T. V. Volchenkova; Ye. V. Isakova; S. V. Kotov (Бюллетень сибирской медицины, 2010)
Influence of the previous antihypertensive therapy on the course of cerebral stroke was analyzed in 188 hypertensive patients. Stroke course features and treatment outcome were analyzed in patients receiving regular antihypertensive therapy before stroke and in those not treated or treated irregularly. Direct influence of previous antihypertensive therapy on the rate of hemorrhagic stroke development, its course severity, and subsequent functional recovery was revealed.